2000
DOI: 10.1097/00003246-200011000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Midazolam and 2% propofol in long-term sedation of traumatized, critically ill patients: Efficacy and safety comparison

Abstract: Propofol's new preparation is safe when used in severely traumatized patients. Its more concentrated formula improves the lipid overload problem seen with the prolonged use of the previous preparation. Nevertheless, a major number of therapeutic failures were detected with 2% propofol because of the need for dosage increase. This fact could be caused by a different disposition and tissue distribution pattern of both propofol preparations. New studies will be needed to confirm these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…A higher number of therapeutic failures because of sedative inefficacy was seen in the propofol group compared with the midazolam group [26]. We also found that two patients had therapeutic failure in group P, due to inadequate sedation at the highest dosage of sedative.…”
Section: Discussionmentioning
confidence: 60%
“…A higher number of therapeutic failures because of sedative inefficacy was seen in the propofol group compared with the midazolam group [26]. We also found that two patients had therapeutic failure in group P, due to inadequate sedation at the highest dosage of sedative.…”
Section: Discussionmentioning
confidence: 60%
“…Of the studies using the Ramsay scale, recommended ranges were 2 to 3 (recommended in two studies [21,22]), 2 to 4 (two studies [23,24]), 2 to 5 (two studies [25,26]), 3 to 4 (two studies [27,28]) and 4 to 5 (one study [29]), while three studies did not recommend specific levels but recommended that levels be optimised for each individual patient [30-32]. This variation was reflected in the other scales used; for studies recommending a modified Ramsay scale, recommended ranges were 1 to 4 [33], 3 to 4 [34], 4 [35], and 5 to 6 (the last range being specifically for seriously injured patients [36]) or targets optimised for each patient [37,38]. The stated SAS (Riker Sedation-Agitation Scale) target level was 1 to 3 [39], 4 [40,41], or 3 to 4 [42].…”
Section: Resultsmentioning
confidence: 99%
“…The remaining included studies comprised studies of sedative drugs [21-26,29,31-34,36,37,39-42,45-50], studies investigating different sedation devices or scales [27,28,38,51,52], and studies looking at the introduction of a sedation guideline or protocol [3,35,53,54]. Studies varied by design and aim, by sedatives used, by scales and definitions of sub-optimal sedation used, and by the way incidence was reported (as a proportion of measurements, patients, or time).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly no significant differences were seen in haemodynamic variables between the two groups. Interestingly, there was a higher incidence of therapeutic failure in the propofol group either because of inadequate sedation or hypertriglyceridemia [33]. Other smaller, underpowered studies have also failed to demonstrate a difference in outcomes between these two agents [34].…”
Section: Benzodiazepinesmentioning
confidence: 99%